2023
DOI: 10.3389/fimmu.2023.1154146
|View full text |Cite
|
Sign up to set email alerts
|

The role of lysosomal peptidases in glioma immune escape: underlying mechanisms and therapeutic strategies

Abstract: Glioblastoma is the most common primary malignant tumor of the central nervous system, which has the characteristics of strong invasion, frequent recurrence, and rapid progression. These characteristics are inseparable from the evasion of glioma cells from immune killing, which makes immune escape a great obstacle to the treatment of glioma, and studies have confirmed that glioma patients with immune escape tend to have poor prognosis. The lysosomal peptidase lysosome family plays an important role in the immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 192 publications
0
2
0
Order By: Relevance
“…Immune evasion is the avoidance of tumor cells being recognized and attacked by the immune system, for example by suppressing the immune response. Gliomas reside in the brain and were previously thought to be immunologically privileged and immune surveillance spared, but recent studies have shown that the brain is an active regulatory point of immune surveillance 57,60 . Without disruption of the BBB, the infiltration of peripheral immune cells into gliomas is very limited.…”
Section: Advances In Chemotherapy For Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…Immune evasion is the avoidance of tumor cells being recognized and attacked by the immune system, for example by suppressing the immune response. Gliomas reside in the brain and were previously thought to be immunologically privileged and immune surveillance spared, but recent studies have shown that the brain is an active regulatory point of immune surveillance 57,60 . Without disruption of the BBB, the infiltration of peripheral immune cells into gliomas is very limited.…”
Section: Advances In Chemotherapy For Gliomamentioning
confidence: 99%
“…Gliomas reside in the brain and were previously thought to be immunologically privileged and immune surveillance spared, but recent studies have shown that the brain is an active regulatory point of immune surveillance. 57 , 60 Without disruption of the BBB, the infiltration of peripheral immune cells into gliomas is very limited. However, when the BBB is disrupted by tumor growth or inflammation, gliomas are infiltrated by immunosuppressive cells.…”
Section: Advances In Chemotherapy For Gliomamentioning
confidence: 99%